Efficacy and safety of direct‐acting antivirals for hepatitis C in the elderly: A systematic review and meta‐analysis. (15th May 2019) - Mücke, Marcus M.; Herrmann, Eva; Mücke, Victoria T.; Graf, Christiana; Zeuzem, Stefan; Vermehren, Johannes
Abstract: Background&Aims: Since the introduction of direct‐acting antivirals (DAAs) several studies have reported high efficacy and safety in Hepatitis C infected patients, even in those earlier considered difficult‐to‐treat. We aimed to assess the efficacy and safety of DAA therapy in elderly patients. Methods: The PubMed MEDLINE, Embase and Cochrane databases were searched through July 2018. Two independent researchers extracted data and assessed the quality and risk of bias. Risk ratios (RRs) were pooled using random effects models. The primary outcome was efficacy of DAA therapy assessed by the RR for non‐sustained virologic response (SVR) among patients aged <65 vs ≥65 years. Results: Overall, we identified 63 studies including 34 082 patients treated with different DAAs. Risk for non‐SVR was comparable in patients <65 and ≥65 years of age (RR 1.00, 95% CI 0.86‐1.15; P = 0.979) and even lower in a subgroup analysis of cirrhotic patients ≥65 years of age (RR 0.59, 95% CI 0.35‐0.99, P = 0.044). Risk for non‐SVR was similar between age groups in all other subgroup analyses. Elderly patients had a significantly increased risk of adverse events (AEs) (RR 1.30, 95% CI 1.11‐1.52, P = 0.001), but not for serious adverse events ( P = 0.43) or treatment discontinuation ( P = 0.15). Risk for anaemia if treated with additional ribavirin was 2.84 (95% CI 1.73‐4.66, P < 0.001) in elderly patients compared to patients <65 years. Conclusion: Our results show that DAAs are highly effective and safe in elderly patients. Ribavirin should be avoided in the elderly as more AEs and particularly anaemia is observed. Further cost‐effectiveness analyses are needed to evaluate the socio‐economic benefit of treating elderly people without advanced liver disease.